2022
DOI: 10.1186/s13054-022-04281-w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high-flow oxygen versus T-piece ventilation strategies during spontaneous breathing trials on weaning failure among patients receiving mechanical ventilation: a randomized controlled trial

Abstract: Background A spontaneous breathing trial (SBT) is used to determine whether patients are ready for extubation, but the best method for choosing the SBT strategy remains controversial. We investigated the effect of high-flow oxygen versus T-piece ventilation strategies during SBT on rates of weaning failure among patients receiving mechanical ventilation. Methods This randomized clinical trial was conducted from June 2019 through January 2022 among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 33 publications
0
12
0
1
Order By: Relevance
“…Of the 19 studies further assessed for eligibility, 9 were excluded (Figure 1). In addition to 31 previously included trials, we identified 10 new full publications, including 1 full publication that replaced a previously included abstract publication. Of the 40 trials included (n = 6797 randomized and n = 6716 patients with outcomes), 9 were new trials (n = 3130 patients analyzed), 6 trials compared 3 SBT techniques (but for 1 of the 3-arm trials, the 5-cm H 2 O and 10-cm H 2 O CPAP groups were combined for a single comparison with the third T-piece group), and 1 trial compared 4 SBT techniques (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 19 studies further assessed for eligibility, 9 were excluded (Figure 1). In addition to 31 previously included trials, we identified 10 new full publications, including 1 full publication that replaced a previously included abstract publication. Of the 40 trials included (n = 6797 randomized and n = 6716 patients with outcomes), 9 were new trials (n = 3130 patients analyzed), 6 trials compared 3 SBT techniques (but for 1 of the 3-arm trials, the 5-cm H 2 O and 10-cm H 2 O CPAP groups were combined for a single comparison with the third T-piece group), and 1 trial compared 4 SBT techniques (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-one trials (52.5%) (5 new and 16 previously included) and 23 trials (57.5%) (6 new and 17 previously included) were judged to be at low risk of bias for randomization and allocation concealment, respectively. Four trials (10.0%) were judged to be at high risk of bias with regard to allocation concealment, including 1 quasi-randomized trial allocating patients based on even or odd days.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations